Frames of reference : aspects of feminism and art. - Couacaud, Sally (Sydney : Artspace, 1991)
Baker, Su ; Binns, Vivienne ; Brassington, Pat ; Brown-Rrap, Julie ; Campbell, Barbara ; Coats, Liz ; Cummins, Rebecca ; Daniels, Dolly Nampijinpa ; Day, Elizabeth ; Dwyer, Mikala ; Fairskye, Merilyn ; Ferran, Anne ; Graham, Anne ; Harris, Ann ; Hoffie, Pat ; Janaczewska, Noëlle ; Jayamanne, Laleen ; Jones, Lyndal ; Joseph, Frances ; Jubelin, Narelle ; Laurence, Janet ; lee, Lindy ; Lohse, Kathe ; Macdonald, Anne ; Mackinnon, Leah ; Mais, Hilarie ; Mifsud, Bette ; Morgan, Margaret ; Mosey, Anne ; Newman, Elizabeth ; Norrie, Susan ; Orr, Jill ; Paterson, Lee ; Richens, Jane ; Rooney, Emma ; Rosser, Margot ; Saul, Shiralee ; Scott, Jill ; Temin, Kathy ; Verschueren, Piki ; Watson, Judy ; Wulff, Ann e.
biog., geselect. ind. & gr. tent., geselect. bibliog. [1 p.] per kunstenaar
English
Frames of reference : aspects of feminism and art, Artspace, Sydney, 15 August - 29 September 1991
kunstcatalogus